Gastrointestinal tract (gut) health in the young pig - Pluske, John R.; Turpin, Diana L.; Kim, Jae-Cheol (Animal Nutrition, 2018)
An optimally functioning gastrointestinal tract (GIT) clearly is of importance to the overall metabolism, physiology, disease status and performance of pigs of all stages of growth and development. Recently, the ‘health’ of the GIT (‘gut health’) has attracted much attention despite the lack of a clear definition to the term or its aetiology, although in broad terms, ‘gut health’ encompasses a number of physiological and functional features including nutrient digestion and absorption, host metabolism and energy generation, a stable and appropriate microbiota/microbiome, defence mechanisms including barrier function and mucosal immune mechanisms, and the interactions between these components. ‘Gut health’ in the newly-weaned (young) pig is of obvious interest due to changes in GIT structure and function associated with the post-weaning transition, and more recently to the upsurge in interest in different feed additives as dietary alternatives/replacements caused by bans/reductions in certain antimicrobial compounds being available in some parts of the world. In the presence of enteric disease(s) after weaning, a deterioration in ‘gut health’ may be synonymous to the overall health of the pig, and although some direct relationships can be drawn between pig performance and efficiency and a ‘healthy’ GIT, sometimes this connection is subtler and less obvious, especially in the absence of overt enteric disease(s). The factors and conditions involved in ‘gut health’ are multifactorial, complex, often poorly described and sometimes incorrectly interpreted, although it is evident that perturbations of the GIT can cause an imbalance and disturb the generalized homeostasis. In addition to any enteric diseases or conditions that might arise as a result of these disturbances, other influences will also impact such as the responses occurring in the GIT in the period immediately after weaning, any changes that might occur after a change in diet, and (or) disruptions to meal patterns and hence the flow of nutrients. Ultimately, ‘gut health’ represents the outcome of the GIT in response to its capacity and ability to respond and adapt to the insults and challenges it encounters.